Letter to the Editor. Urticaria in the Emergency Room: Recommendations for Diagnostic and Therapeutic Approach - Célia Costa; Margarida Gonçalo; Em nome do GPEU – Grupo Português de Estudos de Urticária (Acta Médica Portuguesa, 2017)
N/a.